Altered regional homogeneity and functional connectivity of brain activity in young HIV-infected patients with asymptomatic neurocognitive impairment - Han, Shuai; Aili, Xire; Ma, Juming; Liu, Jiaojiao; Wang, Wei; Yang, Xue; Wang, Xi; Sun, Lijun; Li, Hongjun (Frontiers in Neurology, 2022)
Objective Asymptomatic neurocognitive impairment (ANI) is a predominant form of cognitive impairment in young HIV-infected patients. However, the neurophysiological mechanisms underlying this disorder have not been clarified. We aimed to evaluate the altered patterns of functional brain activity in young HIV-infected patients with ANI by quantifying regional homogeneity (ReHo) and region of interest (ROI)-based functional connectivity (FC). Methods The experiment involved 44 young HIV-infected patients with ANI and 47 well-matched healthy controls (HCs) undergoing resting-state functional magnetic resonance imaging (rs-fMRI) and neurocognitive tests. Reho alterations were first explored between the ANI group and HC groups. Subsequently, regions showing differences in ReHo were defined as ROIs for FC analysis. Finally, the correlation of ReHo and FC with cognitive function and clinical variables was assessed. Results Compared with HCs, ANI patients had a significant ReHo decrease in the right lingual gyrus (LING. R), right superior occipital gyrus (SOG. R), left superior occipital gyrus (SOG. L), left middle occipital gyrus (MOG. L), right middle frontal gyrus (MFG. R), cerebellar vermis, ReHo enhancement in the left middle frontal gyrus (MFG. L), and left insula (INS L). The ANI patients showed increased FC between the LING. R and MOG. L compared to HC. For ANI patients, verbal and language scores were negatively correlated with increased mean ReHo values in the MFG.L. Increased mean ReHo values in the INS. L was positively correlated with disease duration—the mean ReHo values in the LING. R was positively correlated with the abstraction and executive function scores. Increased FC between the LING. R and MOG. L was positively correlated with verbal and language performance. Conclusion The results suggest that the visual network might be the most vulnerable area of brain function in young HIV-infected patients with ANI. The middle frontal gyrus, cerebellar vermis, and insula also play an important role in asymptomatic neurocognitive impairment. The regional homogeneity and functional connectivity of these regions have compound alterations, which may be related to the course of the disease and neurocognitive function. These neuroimaging findings will help us understand the characteristics of brain network modifications in young HIV-infected patients with ANI.